Dance as Hobby Among Dental Students - RAVIKUMAR, HARITA; GANAPATHY, DHANRAJ; SASANKA, L. KEERTHI (The journal of contemporary issues in business and government, 2020)
Dance is an artform that is used to express a person’s feelings. It is a good relaxation and good hobby for people. It has the ability to reduce stress and increase the blood flow of the body. Dental profession is one of the most stressful professions and management is very important. Dental students reported high stress levels which causes mood swings, change in attitude and decreased academic performance. The aim of this study is to analyse the frequency of dance as a hobby among dental students. The study was conducted by preparing questionnaires pertaining to the topic on dance as a hobby among dental students and was circulated through an online survey planet link. Data were collected and analysed. According to the survey, 70.6% of dental students like dancing, 58.4% of them dance very often. 70.2% of them dance to fast beats, 53.9% of them dance due to stress. 72.3% of them feel happy when they dance and 69.2% are passionate towards dancing. Dance is enjoyed by many as a hobby. But due to lack of time and workload, many are not able to continue dancing.